ECONOMIC ASSESSMENT OF SOME AGRO FORESTRY SYSTEMS AND ITS POTENTIAL FOR CARBON SEQUESTRATION SERVICE IN INDONESIA - Kirsfianti L. Ginoga; Y. Cahya Wulan; Mega Lugina; Deden Djaenudin (Secretariat of Agency for Standardization of Environment and Forestry Instruments, 2004)
This paper provides several alternatives agroforestry and plantation systems to consider for carbon sequestration purposes. It is indicated that multicropping of coffee multistrata or fruit trees such as mango, duku and durian with timber or food and vegetable crops produces more benefits financially and economically compared to monoculture of tree plantation such as albizia. The former system is more attractive in terms of return to labour and land. However, the later system produce more carbon and low cost of carbon, which is more potential from the buyers point of view: So there is a trade-off from supply and demand side for choosing the best alternatives system. Implication of these are as follows: (i) amount and price of product is becoming a key factors in determining whether a system is more feasible for selling of product or carbon trade, and (ii) there is a need to create incentives system for land owners/producers if carbon trade is a priority.